Katalis Calcium Oxide Dari Cangkang Kerang Simping Untuk Sintesis Biodiesel Berbasis Minyak Jelantah - Abdul Haris Mulyadi; Author Muhammad Arkan Naufal (UM Purwokerto Press, 2026)
The utilization of waste into high-value materials is one solution to environmental and energy issues. This study aims to examine the effect of catalyst size on the yield of biodiesel synthesized from used cooking oil with the aid of calcium oxide catalyst from simping shell through transesterification at 65? for 2 hours. The independent variables studied were catalyst particle size (0.180, 0.150, 0.125, 0.075, and 0.063 mm). The results showed that a catalyst particle size of 0.125 mm gave the best results, with a yield of 43.24%. The biodiesel product met the SNI 7182:2015 standard with a FAME content of 98.01% and an acid number of 0.453 mg-KOH/gram.